Biology of Activating Transcription Factor 4 (ATF4) and Its Role in Skeletal Muscle Atrophy. Issue 4 (27th December 2021) - Ebert, Scott M; Rasmussen, Blake B; Judge, Andrew R; Judge, Sarah M; Larsson, Lars; Wek, Ronald C; Anthony, Tracy G; Marcotte, George R; Miller, Matthew J; Yorek, Mark A; Vella, Adrian; Volpi, Elena; et al.
ABSTRACT: Activating transcription factor 4 (ATF4) is a multifunctional transcription regulatory protein in the basic leucine zipper superfamily. ATF4 can be expressed in most if not all mammalian cell types, and it can participate in a variety of cellular responses to specific environmental stresses, intracellular derangements, or growth factors. Because ATF4 is involved in a wide range of biological processes, its roles in human health and disease are not yet fully understood. Much of our current knowledge about ATF4 comes from investigations in cultured cell models, where ATF4 was originally characterized and where further investigations continue to provide new insights. ATF4 is also an increasingly prominent topic of in vivo investigations in fully differentiated mammalian cell types, where our current understanding of ATF4 is less complete. Here, we review some important high-level concepts and questions concerning the basic biology of ATF4. We then discuss current knowledge and emerging questions about the in vivo role of ATF4 in one fully differentiated cell type, mammalian skeletal muscle fibers.